Symptoms of the planetary condition a critical vocabulary - Bunz, Mercedes 1971-; Kaiser, Birgit Mara 1971-; Thiele, Kathrin 1972- (meson press, 2017)
This book explores the future of critique in view of our planetary condition. How are we to intervene in contemporary constellations of finance capitalism, climate change and neoliberalism?
Keywords: Klimaänderung; Neoliberalismus; Gefahr; Kapitalismus; Wörterbuch